1968
DOI: 10.1104/pp.43.11.1747
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Root Exudates in a Steril Continuous Flow Culture. II. Short-Term and Long-Term Variations of Exudation Intensity

Abstract: Abstract. The exudate production of alfalfa under the conditions of the sterile flow culture was quantitatively measured. In the first 40 days 3.10-3 ,mmoles amino-N, 2.5 ,,uequivailents of organic acids and approximately l04 ,moles of reducing sugars were liberated per plant and per day into the percolating nutrient solution. The amino acid concentration in the outflow varies according to a daily periodicity. The exudation of a colored substance also shows daily periodical variations. This pattern is d6iffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…The increase in N exudation at a high temperature (35~ (Table 6) may also be attributed to the increase in root metabolic activities or changes in the membrane permeability. This assumption is supported by the fact that, in soybean and sesbania, N exudation per unit root dry weight was higher at 35~ than at 15 and 25~ (Table 6b), while in chinese milk vetch, N exudation per unit root weight was highest at 15~ Richter et al (1968) observed that the depression of the respiration rate induced by the respiratory poison, dinitrophenol attenuated the loss of some amino acids, suggesting the presence of a correlation between root exudation and metabolism.…”
Section: Discussionmentioning
confidence: 76%
“…The increase in N exudation at a high temperature (35~ (Table 6) may also be attributed to the increase in root metabolic activities or changes in the membrane permeability. This assumption is supported by the fact that, in soybean and sesbania, N exudation per unit root dry weight was higher at 35~ than at 15 and 25~ (Table 6b), while in chinese milk vetch, N exudation per unit root weight was highest at 15~ Richter et al (1968) observed that the depression of the respiration rate induced by the respiratory poison, dinitrophenol attenuated the loss of some amino acids, suggesting the presence of a correlation between root exudation and metabolism.…”
Section: Discussionmentioning
confidence: 76%
“…Root exudates of corn (Zea mays L.) were analyzed after 8 and 16 days' growth for changes in carbohydrate composition by Arkadeva (1963a (Smith and Peterson 1966). Richter et al (1968) (Arkadeva 1963b;Balasubramanian and Rangaswami 1969;Rovira I956q;Rovira 1959;Schreiber and Green 1963 (Adams et al 1968;Schroth et al 1963;Smith and Peterson 1966 Jones (1943) has reported that the grand period of growth for transient or no{r-cambial roots of alfalfa ends with the onset of flowering and is followed by a period of inactivity and root disintegration. It has been suggested that the development of flower primordia in grasses has a deleterious effect on root development (Stucky 1941 …”
mentioning
confidence: 99%
“…by the association Rhizobium and legumes can be transferred to forage grass species through different pathways, including exudation, senescence, and degradation or direct transfer of N from legume to non-legume roots (Richter et al, 1968). Despite the vast body of literature indicating the benefits associated with legumes in mixed swards, widespread utilization of tropical legumes worldwide is still scarce.…”
Section: Herbage Characteristics Of Pintoi Peanut and Paslisadegrass mentioning
confidence: 99%
“…by the association Rhizobium and legumes can be transferred to forage grass species through different pathways, including exudation, senescence, and degradation or direct transfer of N from legume to non-legume roots (Richter et al, 1968).…”
mentioning
confidence: 99%